Psychological tools used for monitoring training responses of athletes? - Nässi, A.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M. (Performance Enhancement & Health, 2017)
Monitoring athletes` responses to training and other life stressors is crucial for implementing favourable training routines and achieving optimal performances. The purpose of this review is to provide an overview and evaluation of current psychological tools used in training contexts among athletes. The instruments discussed include the Profile of Mood States (POMS), the Emotional Recovery Questionnaire (EmRecQ), the Total Quality Recovery (TQR) scale, the Daily Analyses of Life Demands for Athletes (DALDA), the Recovery-Stress Questionnaire for Athletes (RESTQ-Sport), the Acute Recovery and Stress Scale (ARSS), the Short Recovery and Stress Scale (SRSS), and the Multi-Component Training Distress Scale (MTDS). Each measure has been shown to deliver valuable information for athletes and coaches regarding individual responses to training. These responses are measured by observing changes in mood, emotions, perceived stress and recovery, and sleep quality. Practitioners need to consider the appropriateness of each psychological tool in the context of their particular group. Regardless of which methods are employed, care should be taken to employ measurement in a systematic manner, provide timely feedback, and consider frequency as not to burden athletes too much. While psychological measures are an important part of avoiding maladaptive training responses, performance and physiological changes also need to be taken into account.